Building Center Health Program at Indonesian Preschool (Prospect & Challenges) - Mukminin, Amirul; Arso, Septo Pawelas (Universitas Negeri Semarang, 2015)
UKS (Usaha Kesehatan Sekolah) is very important as a learning media to improve healthy life ability and to build healthy life behavior of students at the school. UKS program management has not been maximal, including planning, organizing, operating, and evaluating. The aim of this study is to explain the functions of planning, organizing, operating, and supervising in UKS at preschools in Semarang City. This study used observational research method with a qualitative approach. The data collecting used the deep interview to four UKS trainer teachers at preschools, with the criteria: the school having good and fair UKS programs as the main informants, and three employees of UKS Puskesmas (Pusat Kesehatan Masyarakat), and one employee of UKS Education Service as the triangulation informants. The result of the study shows that the UKS program management had not run well because many schools did not make the planning of activity type, activity schedule, fee, tool needs, and medicine. However, all of the schools made the planning of the number of the employee. The function of organizing had not run well although they had done the activity of resource decision, authority delegation, and coordinating. However, not all of them had done the job description of working group. The function of UKS program implementation was not also good enough. Although all schools had employees and students preparation as well as the service, many schools had not given the service maximally. The service was only given when there was a program from Puskesmas. The function of supervision was not good because many schools had not received supervision, there was no any evaluation and did not report the UKS program. It is suggested that the head and the UKS Trainer Board supervise intensively to the UKS program implementation so that it can motivate the schools to do UKS program in a good and proper way. The Health Service of Semarang City and the Education Service of Semarang City must broaden the relationship with others.How to citeMukminin, A., & Arso, S. (2015). Building Center Health Program at Indonesian Preschool (Prospect & Challenges). Indonesian Journal Of Early Childhood Education Studies, 4(1), 67-73. doi:10.15294/ijeces.v4i1.9455